Efficiently-managed Cloudly-Secured Mobile User Data Sharing Code Implementation - Naeem Th. Yousir,; Sami Hasan, (Iraqi Journal of Science, 2021)
Increasing Mobile Device on Cloud Technology will dominate the various industries. Cloud has different data storage and data protecting techniques that based on Data User (DU) and industry’s needs. In this paper, an efficient way of managing user data sharing via Mobile Agent (MA) also called Mobile Proxy (MP) is proposed. The role of Mobile Agent Authorize User to collect the data from Cloud like Proxy and supply data to another Client due to this missing of cloud data is not possible. Instead of access data for all clients, the proxy hold required data and share the customer because of this network reliability, Network Bandwidth, User Congestion, Data Security. Also, this proposed scheme have more functionality like Cloud Authentication, Data Owner (DO) Sending files to Cloud, Sending password, Send Mail and Send SMS. Suppose Data Users need to communicate and share information on Cloud with the help of Mobile Agent only. So, Data Users may be assured that whatever resource required in the cloud with the documents on their Mobile Agent in the office